2018
DOI: 10.1158/0008-5472.can-17-1904
|View full text |Cite
|
Sign up to set email alerts
|

ER Stress Signaling Promotes the Survival of Cancer “Persister Cells” Tolerant to EGFR Tyrosine Kinase Inhibitors

Abstract: An increasingly recognized component of resistance to tyrosine kinase inhibitors (TKI) involves persistence of a drug-tolerant subpopulation of cancer cells that survive despite effective eradication of the majority of the cell population. Multiple groups have demonstrated that these drug-tolerant persister cells undergo transcriptional adaptation via an epigenetic state change that promotes cell survival. Because this mode of TKI drug tolerance appears to involve transcriptional addiction to specific genes an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 57 publications
4
71
0
Order By: Relevance
“…53 It has been shown that ER stress induces activation of SREBP2 and a subsequent cholesterol accumulation in cancer cell lines. 56 Taken together, these studies highlight the possibility that EGFR TKI induced ER stress is causing activation of SREBP2 and subsequent activation of cholesterol synthesis ( Figure 6). 55,56 Another study found that erlotinib-induced ER stress signaling can promote the survival of EGFR TKI-persister cells after exposure to erlotinib through transcriptional adaptation via an epigenetic state change.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…53 It has been shown that ER stress induces activation of SREBP2 and a subsequent cholesterol accumulation in cancer cell lines. 56 Taken together, these studies highlight the possibility that EGFR TKI induced ER stress is causing activation of SREBP2 and subsequent activation of cholesterol synthesis ( Figure 6). 55,56 Another study found that erlotinib-induced ER stress signaling can promote the survival of EGFR TKI-persister cells after exposure to erlotinib through transcriptional adaptation via an epigenetic state change.…”
Section: Discussionmentioning
confidence: 82%
“…In our model we found upregulation of SREBP2, which is a transcription factor that controls the transcription of cholesterol synthesis genes. 55,56 Another study found that erlotinib-induced ER stress signaling can promote the survival of EGFR TKI-persister cells after exposure to erlotinib through transcriptional adaptation via an epigenetic state change. 54 EGFR TKI-treatment has been linked to the induction of ER stress response and this is one of the reasons that patients experience diarrhea as a common side effect of EGFR TKIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of STING subsequently induces upregulation of its downstream cytokines, including type I interferon and CXCL10, which promotes T-cell-mediated therapeutic antitumor immunity via enhancing neoantigen presentation and T-cell recruitment into the TME [100]. Not only DNA damage accumulation but also excessive ER stress activate the STING pathway [101]. Considering these mechanisms, it is not surprising that the increased genomic instability and metabolic stress that accumulates in RB-inactive cancer cells potentiate the efficacy of immunotherapy in certain contexts.…”
Section: Therapeutic Strategy Targeting Innate Immune Signaling In Rbmentioning
confidence: 99%